OZONE AS A COLLAGEN BIO-STIMULATOR: CASE REPORT - Batista Pereira Gomes do Nascimento, Beatriz; Rech Feldmann, Cristina (Health and Society, 2022)
The search for a skin similar to that obtained through filters of social networking applications is increasingly present in the complaints and desires of patients who arrive at the office. As the skin is the organ that most reflects the effects of the passage of time, in addition to genetic factors, hormonal status and metabolic reactions, such as oxidative stress, your health and appearance are directly related to the eating habits and the chosen lifestyle. The current challenge is the search for minimally invasive facial rejuvenation treatments with a lower risk of complications. A clinical case was reported in this article using only ozone applied subcutaneously to the submental region and neck. Clinical case: patient I.V, female, 60 years old, sought a private practice complaining of sagging skin in the papillae and neck region that bothered her. After careful examination and skin evaluation, it was proposed to the patient that we start the collagen induction protocol with ozone. Thus, we can conclude that the use of this aforementioned technique is an excellent alternative (safe and effective) for a more youthful and rejuvenated skin.